A critical examination of concept analysis and its application to concepts of space in geography - Welch, Sally Lynn (Rhodes University, Faculty of Science, Department of Geography, 1981)
Preface: Concept analysis utilising Piaget and Gagne's theories is an expanding area of research in the 'exact' sciences such as physics and chemistry. It is, however, new to the concepts in geography which are 'non-exact'. The thesis, then, is an exploratory study; and concept analysis is considered a possible methodology for examining the students' understanding of non-exact geography concepts. The thesis is divided into two parts. The first contains an examination of the theory of concept analysis and a critical review of empirical studies, with a view to applying concept analysis to the discipline of geography. The second part involves what has been termed a case study, where concepts are selected for analysis, and students were tested for their understanding of the concepts.
Keywords: Space perception; Geography -- Methodology